2014
DOI: 10.1051/0004-6361/201424447
|View full text |Cite
|
Sign up to set email alerts
|

The triple near-Earth asteroid (153591) 2001 SN263: an ultra-blue, primitive target for the Aster space mission

Abstract: Context. The Brazilian Aster project plans a space mission to rendezvous and characterize (153591) 2001 SN263, one of the only two known triple near-Earth asteroids (NEAs). Improving the knowledge of its physical properties is necessary to optimize the mission planning and science return. Aims. We study the surface composition and physical nature of 2001 SN263 by analyzing and comparing its reflectance spectra with laboratory spectra of minerals and meteorites. Methods. We performed spectroscopic observations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Our spectral analysis agrees with that of Perna et al (2014). More extensive spectral coverage results in a more definitive taxonomic class identification.…”
Section: Spectrasupporting
confidence: 82%
See 1 more Smart Citation
“…Our spectral analysis agrees with that of Perna et al (2014). More extensive spectral coverage results in a more definitive taxonomic class identification.…”
Section: Spectrasupporting
confidence: 82%
“…The combined spectrum of Bennu is shown for comparison, offset for clarity. SN 263 inclined by6:7 (Minor Planet Center, 2001;Perna et al, 2014). These similarities may suggest a common origin, and the samples expected from Bennu may be similar in composition to objects like 2001 SN 263 .…”
mentioning
confidence: 91%
“…On September 20th of 2001 the LINEAR survey discovered the asteroid (153591) 2001 SN263 (Stokes et al 2000). Radar observations made by the Arecibo Observatory on February 12th of 2008, when it made its closest approach to Earth at a distance of 0.06558 au, revealed it is composed of three components (Nolan et al 2008). Early spectroscopic observations indicated that it is a B-type asteroid in the Bus-DeMeo taxonomy (DeMeo et al 2009).…”
mentioning
confidence: 99%
“…Later, Perna et al (2014) investigated the surface composition of the asteroid 2001 SN263 and compared its reflectance spectra with laboratory spectra of meteorites and minerals. They found a featureless convex spectrum (Polanaor Themis-like), confirming it as a B-type.…”
mentioning
confidence: 99%
“…A previous classification of this binary was performed by Perna et al (2014) who found it to be B type.…”
Section: A22 (153591) 2001 Sn 263mentioning
confidence: 99%